2021
DOI: 10.2298/vsp190502132k
|View full text |Cite
|
Sign up to set email alerts
|

The influence of personality traits and coping strategies on the quality of life of patients with relapsing-remitting type of multiple sclerosis

Abstract: Introduction/Aim: Multiple sclerosis (MS) is a chronic and progressive autoimmune disease of the central nervous system that can reduce the quality of life. Personality traits and coping strategies are a significant factor in interpersonal variance regarding quality of life. The aim of this study was to examine relations between personality traits and coping strategies in patients with relapsing-remitting (RR) type MS, and to examine relations of personality traits, coping strategies and quality of life in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
1
0
1
Order By: Relevance
“…Particularly, Bassi et al (2021) found a negative association between avoidance coping and physical HRQOL. In addition, Cerea et al (2021) discovered a positive association between mental HRQOL and problem solving and a negative with emotional discharge and passive coping (Cerea et al, 2021;Krstić et al, 2021). The scientific literature revealed that MS patients use less active and more avoidance and emotional coping than the general population (Keramat Kar et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, Bassi et al (2021) found a negative association between avoidance coping and physical HRQOL. In addition, Cerea et al (2021) discovered a positive association between mental HRQOL and problem solving and a negative with emotional discharge and passive coping (Cerea et al, 2021;Krstić et al, 2021). The scientific literature revealed that MS patients use less active and more avoidance and emotional coping than the general population (Keramat Kar et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…13 Καθώς η ΠΖ αντικατοπτρίζει σε έναν βαθμό και το επίπεδο προσαρμογής του ατόμου στις συνθήκες που βιώνει, θα πρέπει να αναζητήσουμε ανάμεσα στους παράγοντες που την επηρεάζουν και τους πιθανούς ψυχολογικούς προσαρμοστικούς μηχανισμούς. Ο ρόλος διαφόρων διαστάσεων της προσωπικότητας στην ΣΥΠΖ έχει ερευνηθεί αρκετά σε σχέση με την ΠΣ, [14][15][16][17] όχι όμως και των αμυντικών μηχανισμών του Εγώ, παρότι έχει αναδειχθεί η σημαντικότητά τους σε διάφορες άλλες χρόνιες ασθένειες. [18][19][20][21][22] Πρώτος ο Sigmund Freud εισήγαγε τον όρο ¨άμυνα¨2 3 στα τέλη του 1800.…”
unclassified